Endoscopic transcanal transtympanic myringoplasty vs. endoscopic transcanal tympanoplasty: 1-year follow-up study. Issue 10 (12th July 2022) - Chen, Chin-Kuo; Kuo, Chin-Lung; Weng, Yu-Ting; Hsieh, Li-Chun
Abstract : Background: Endoscopic transcanal transtympanic myringoplasty (ETTM) is a relatively easier technique than endoscopic transcanal tympanoplasty (ETT) for repairing tympanic membrane perforations. No studies have compared the outcomes of these two procedures with tragal perichondrium after 1-year. Furthermore, there is no evidence-based stratification according to variations in perforation size in endoscopic ear surgery. Therefore, we compared the 1-year outcomes of ETTM and ETT stratified according to perforation size. Methods: Patients who underwent ETT and ETTM to repair eardrum perforations with a tragal perichondrium graft were identified. Pure-tone audiometric tests and otoscopic examination were performed to assess hearing outcomes and perforation sizes both preoperatively and at least 1 year postoperatively. Results: In total, 158 patients (159 ears) were included. ETT was performed on 83 ears, and ETTM was performed on 76 ears. The ETTM procedure time was 10-minutes shorter than that for ETT ( p < 0.001). Perforation size was significantly correlated with graft take-rate. For large perforations, the ETT success rate was significantly higher than that of ETTM (91.7% vs. 78.9%). Success rates for small-medium perforations were comparable for both methods ( p > 0.05). However, for medium perforations, the graft take-rate of ETT reached a plateau after 6 months, while that of ETTM gradually declined during the 12-month follow-up. Both groups had a comparable mean postoperative air-bone gap gain ( p = 0.666). Conclusion: ETTM is suitable for repairing small perforations, whereas ETT is preferred for large perforations. Both methods, and particularly ETTM, should be employed cautiously for medium perforations.